Médeia, az alkimista: Girolamo Macchietti festményéről és a Médeia-ábrázolások alapproblémájáról - Bódi, Katalin (Studia Litteraria, 2017)
The figure of Medea (well known from the Metamorphoses of Ovid and from the tragedies of ancient literature) does not have a special iconography in the early modern era, which can be the consequence of her complicated story in the different works. In my opinion, the painting of Girolamo Macchietti is an example for the actualization of the story according to the ideology of the Renaissance era about man and nature: the power of human knowledge and the complexity of the world. The representation of Medea as a magician offers a direct connection between the painting and Ovid’s Metamorphoses, but the place of Girolamo Macchietti’s work can extend the interpretation. The painting was ordered beside many others by Francesco I de’ Medici for his studiolo, which was a working room and a place for his collections. The scholar Vicenzo Borghini designed the decoration of the studiolo to celebrate the relation between Art and Nature in accordance with the personal interests of Francesco, such as alchemy, among others. But the painting does not show these references explicitly anymore: therefore my paper tries to reconstruct the forgotten contexts surrounding the painting and the figure of Medea.